Sistem Charger Station Handphone Dilengkapi dengan Fitur Monitoring dan Radio Frequency Identification - Nadia Ulfa; Muhammad Rusardi; Hilmayuda; Jamilah; Sinek Mehuli Br Perangin-Angin; Asprina Br Surbakti (Prodi Teknik Informatika (S1) Institut Teknologi dan Bisnis Indonesia, 2023)
Safety in charging cellphone batteries in public places is the most important thing. Places for charging cellphone batteries / Charger stations in public places do not have a good security system so that there are many cases of cellphone theft and so on. A charger station is very important to have security features to avoid these unwanted things. Therefore the use of the RFID (Radio frequency identification) feature is the right thing to make a security system at the charger station. This charger station system uses an Atmega 328 microcontroller to process data and control RFID, LED, and other components.